Pelaksanaan Teknik Supervisi dalam Upaya Meningkatkan Kinerja Guru di SMPN 2 Jerowaru - Muhamad Zaril Gapari (MANAZHIM, 2021)
Education is one of the universal activities in human life, wherever there is society, there is education too. Many countries admit that the problem of education is a complicated problem, but all feel that education is a very important task of the State, a nation that wants to progress, build, and try to improve the condition of society and the world, of course, state that education is the key, and without the key their efforts will failed. The objectives of this research which are to be achieved are: (1) To determine the implementation of supervision techniques in an effort to improve teacher performance at SMP Negeri 2 Jerowaru . (2) To determine the impact of supervision to the improved performance tacher SMP Negeri 2 Jerowaru. The type of research used is descriptive qualitative research methods , data collection techniques using interview techniques , observation, and documentation. To obtain data in the field , interviews were conducted with the supervisors and teachers of Jerowaru State Junior High School . The data analysis technique used is the Hubermen and Miells method, namely data reduction, data presentation, and verification or conclusion drawing. The results of this study indicate that in the implementation of the supervision technique, several methods are used, namely, individual techniques and group techniques . Based on these results, intensive coaching efforts are needed in increasing the competence of teachers, school principals, and school supervisors to achieve quality education, starting from improving the quality of the learning process which will ultimately improve the quality of graduates at all types and levels of education.